Decreased Smoke Detector Performance Functionon MV. Sarah S: Menurunnya Fungsi Kinerja Smoke Detectordi atas Kapal MV. Sarah S - Siregar, Reski Hamonangan; Kurniawan, Dedi; Nurmala, Eka; Sultan; Saifudin, Iksan (ATRIA: Jurnal Multidisiplin Riset Ilmiah, 2024)
Ships are vessels used for transporting passengers and goods across bodies of water, such as rivers and seas, using canoes or smaller boats. Fires on ships can occur due to various reasons, including interference with electrical and electronic equipment, as well as flammable liquids like gasoline, grease, and gas leaks. This study adopts a descriptive qualitative approach, utilizing data collection methods such as direct field observation, in-depth interviews with involved parties, and documentation/library research. The research findings highlight two main points: 1) The factors leading to decreased functionality of fire alarm sensors are the lack of maintenance and repair of the system; and 2) A decreased fire alarm system may fail to detect fire or smoke in specific areas, potentially leading to accidents or severe damage to the ship.